2007
DOI: 10.1210/en.2007-0599
|View full text |Cite
|
Sign up to set email alerts
|

Premature Estrogen Exposure Alters Endometrial Gene Expression to Disrupt Pregnancy in the Pig

Abstract: Establishment and maintenance of pregnancy in the pig involve intricate communication between the developing conceptuses and maternal endometrium. Conceptus synthesis and release of estrogen during trophoblastic elongation are essential factors involved with establishing conceptus-uterine communication. The present study identified endometrial changes in gene expression associated with implantation failure and complete pregnancy loss after premature exposure of pregnant gilts to exogenous estrogen. Gilts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
4
46
0
Order By: Relevance
“…These efforts, along with global gene expression studies, have tremendously advanced our understanding of porcine pregnancy and endometrial biology. In recent years, while many global gene expression studies in the porcine endometrium have been conducted on differential gene expression during pregnancy [11][12][13][14], there are very few reports regarding global changes in porcine endometrial proteome during pregnancy [6,15]. Kayser et al [6] reported changes in uterine fluid proteome during early porcine pregnancy and some proteins reported by them are common to this study.…”
mentioning
confidence: 56%
“…These efforts, along with global gene expression studies, have tremendously advanced our understanding of porcine pregnancy and endometrial biology. In recent years, while many global gene expression studies in the porcine endometrium have been conducted on differential gene expression during pregnancy [11][12][13][14], there are very few reports regarding global changes in porcine endometrial proteome during pregnancy [6,15]. Kayser et al [6] reported changes in uterine fluid proteome during early porcine pregnancy and some proteins reported by them are common to this study.…”
mentioning
confidence: 56%
“…The expression patterns of OCT4, IFN , and CDX2 during early embryonic development allow assessment of the quality of blastocysts produced (Bauer et al, 2010;Ross et al, 2007). In ruminant, the function of IFN is the recognition of pregnancy (Bazer et al, 2008) and IFN gene expression is higher in hatched blastocysts than in expanded and early embryos (Rekik et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These estrogens also modulate expression of uterine genes considered essential for implantation, and inappropriate exposure of the pregnant uterus to estrogen on days 9 and 10 results in degeneration of pig conceptuses by day 15 (Ross et al 2007). Both PGE 2 and lysophosphatidic acid (LPA) have proposed roles in pregnancy recognition signaling.…”
Section: Ifns Estrogens and Uterine Receptivity To Implantation In mentioning
confidence: 99%
“…High levels of IFNG may act on uterine stroma and GE to increase intracellular interferon-stimulated gene factor 3 (ISGF3) that permits lower levels of IFND to maximally upregulate STAT1 expression in close proximity to the implanting pig conceptus. To date, a limited number of estrogen-and IFN-stimulated genes have been localized in pig endometrium (see Hicks et al 2003, White et al 2005, Joyce et al 2007a, 2007b, Ka et al 2007, Ross et al 2007, So et al 2008, Song et al 2009). Type I and type II IFNs each induce expression of largely nonoverlapping sets of genes and they may also have synergistic interactions to affect physiological responses (see Levy et al 1990).…”
Section: Ifns Estrogens and Uterine Receptivity To Implantation In mentioning
confidence: 99%